Millennium Challenge Corporation: Interpretations and Implications for the National Security of Nepal - Adhikari, Ashish (Unity Journal, 2022)
The interpretations of MCC in the Nepali “bazaar” comprise three themes: sovereignty, geopolitics, and governance. This study reveals that these diverging interpretations of MCC, based upon these themes, pose implications to the national security of Nepal. Firstly, it poses a challenge to the unity of the Nepalese people. Second, the composed narratives of the United States against China under a geopolitical theme construct another challenge in the conduct of Nepal’s foreign policy. Last, the absence of interpretations based on economic development perspectives creates a socio-economic challenge related to poverty and unemployment. Formal political synonymy, disdain of United States against China narrative, and new narratives of development are crucial to gradually disparage these challenges. Epistemologically, this paper is interpretative (constructive) and uses an inductive, qualitative method of study. To do so, it collects secondary data in the form of expert interviews from the social, political, legal, and economic spaces of society.